2023
DOI: 10.1038/s41598-023-36083-7
|View full text |Cite
|
Sign up to set email alerts
|

Profile of sleep disturbances in patients with recurrent depressive disorder or bipolar affective disorder in a tertiary sleep disorders service

Panagis Drakatos,
David O’Regan,
Yingqi Liao
et al.

Abstract: Bidirectional relationship between sleep disturbances and affective disorders is increasingly recognised, but its underlying mechanisms are far from clear, and there is a scarcity of studies that report on sleep disturbances in recurrent depressive disorder (RDD) and bipolar affective disorder (BPAD). To address this, we conducted a retrospective study of polysomnographic and clinical records of patients presenting to a tertiary sleep disorders clinic with affective disorders. Sixty-three BPAD patients (32 fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Overall, we propose that our results support the feasibility of automatic differential diagnosis of dream narratives based on word-by-word speech graph analysis ( Figure 2 ). 36 Interestingly, it has been shown that schizophrenia and bipolar affective disorder patients, both previously associated with significant changes in sleep architecture, 21 , 45 respond in a reciprocal manner to the dream-report task. For instance, the former were reported to sustain flattened speech, whereas the latter responded to increased confabulation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Overall, we propose that our results support the feasibility of automatic differential diagnosis of dream narratives based on word-by-word speech graph analysis ( Figure 2 ). 36 Interestingly, it has been shown that schizophrenia and bipolar affective disorder patients, both previously associated with significant changes in sleep architecture, 21 , 45 respond in a reciprocal manner to the dream-report task. For instance, the former were reported to sustain flattened speech, whereas the latter responded to increased confabulation.…”
Section: Discussionmentioning
confidence: 99%
“… 15 , 16 More specifically, sleep parasomnias, such as NREM parasomnia (NREMP) 5 , 9 , 17 , 18 and (idiopathic) REM sleep Behavior Disorder (iRBD), 19 , 20 exemplify a rare opportunity to gain a direct insight into dream activity and mentation. 1 , 6 , 16 , 21 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations